Sustainable Risk Management Strategy Selection Using a Fuzzy Multi-Criteria Decision Approach - Galvez-Manriquez, D (Elsevier Ltd, 2020)
While several studies focused on the evaluation of risk management strategies to select the sustainable ones using multi-criteria analysis, most of these studies did not necessarily dealt with the integration of uncertainties. In a context where uncertainties are inherent to natural hazards management decision-making process, the challenge is to systematically take uncertainties into account throughout the assessment process in order to avoid biased decisions. This paper attempts to tackle this challenge by suggesting a methodological approach based on the application of fuzzy multi-criteria decision-making methods. Uncertainties are addressed in two main ways. First, fuzzy AHP is used to estimate the importance of each of the evaluation criteria. Then, fuzzy weighted arithmetic mean method or fuzzy PROMETHEE are used to prioritize the strategies regarding the set of criteria, considering a compensatory or non-compensatory reasoning in order to derive final ranking. This approach is tested in a case study proposing sensitivity analysis in order to study the impact of the compensation phenomenon and the integration of uncertainty in the choice of a sustainable risk management strategy. This hybrid fuzzy multi-criteria decision approach provides a structured framework for identifying the most sustainable strategy under uncertainty. © 2020 Elsevier Ltd